Epidermal growth factor receptor as a molecular determinant of glioblastoma response to dopamine receptor D2 inhibitors. Issue 3 (24th August 2020) - He, Yuyu; Li, Jie; Koga, Tomoyuki; Ma, Jun; Dhawan, Sanjay; Suzuki, Yuta; Furnari, Frank; Prabhu, Varun V; Allen, Joshua E; Chen, Clark C
Abstract: Background: There are ongoing clinical trials exploring the efficacy of dopamine receptor D2 (DRD2) inhibition against glioblastomas, the most common primary brain tumor. Here we examine potential molecular determinants of this efficacy. Methods: The Cancer Genome Atlas glioblastoma database and other published mRNA profiles were used to analyze the DRD2 and epidermal growth factor receptor (EGFR) expression pattern. In vitro and in vivo responses to DRD2 inhibitors were determined using patient-derived xenograft (PDX) glioblastoma models. Immunohistochemical studies were performed on clinically annotated glioblastoma samples derived from patients treated with ONC201. Results: Analysis of clinical glioblastoma specimens derived from independent patient cohorts revealed an inverse correlation between EGFR and DRD2 mRNA expression, with implication that signaling mediated by these proteins shares overlapping functions. In independent panels of PDX glioblastoma lines, high EGFR expression was associated with poor in vitro and in vivo response to DRD2 inhibitors, including haloperidol and ONC201. Moreover, ectopic expression of a constitutively active EGFR, variant (v)III, suppressed glioblastoma sensitivity to ONC201. DRD2 expression positively correlated with expression of rate-limiting enzymes for dopamine synthesis as well as dopamine secretion, suggesting contribution of autocrine DRD2 signaling. Analysis of specimens from patients treated with ONC201 ( n = 15) showed an inverse correlation between the intensity of EGFR staining and clinical response. The median overall survival for patients with high and low EGFR staining was 162 and 373 days, respectively (0.037). Conclusions: High EGFR expression is a determinant of poor glioblastoma response to DRD2. This finding should inform future clinical trial designs.